BEST PRACTICES OF GOOD GOVERNANCE - RELATIONSHIP BETWEEN THE PRINCIPLES OF GOVERNANCE AND THE ETHICAL CONDUCT - Samsuri, Suraya (2011)
Good corporate governance and ethical practices are no longer optional but instead has gradually becoming part of the laws. No doubt that ‘Code of Ethics’ is good for refinement of corporate governance, in fact, each country or organization does nurture its own distinctive code of ethics based on the core values of the societies or businesses. However, even with numerous initiatives undertook in instilling and inculcating good values, ethical conduct, integrity and efforts to avoid potential malpractice; streamlining these efforts to become the norm and culture of the society itself are still the utmost challenge. Ethical norms can provide a sensible basis to create or to solve problems on corporate governance and corporate responsibility and combat the deficit of ethics in the practices of corporate governance especially if the model exemplary is those from the top management’s level. Only those that able to realise the harmonization of ethic, and embedded it with these core values are able to fulfil the obligatory standard required. The aimed of this paper is to fill the gap in the exploration of ethics in the context of corporate governance practices. This is paper is thus a review of academic literature on the range of theories and its implementation from the Asian best practices experience based on the governance pillars – Responsibility, Accountability, Fairness and Transparency.